RNA systems biology: uniting functional discoveries and structural tools to understand global roles of RNAs. (June 2016) - Strobel, Eric J; Watters, Kyle E; Loughrey, David; Lucks, Julius B
Graphical abstract: Highlights: We review recent progress in uncovering the global roles of RNAs across the cell. Regulatory RNAs are more ubiquitous and play more global, networked roles than previously thought. 'RNA structomics' allows cellular RNA structure to be characterized across transcriptomes. New ways in which RNA structures globally regulate cellular processes have been uncovered. RNA structomics is enabling progress in understanding the role of RNA misfolding in human disease. Abstract : RNAs assume sophisticated structures that are active in myriad cellular processes. In this review, we highlight newly identified ribozymes, riboswitches, and small RNAs, some of which control the function of cellular metabolic and gene expression networks. We then examine recent developments in genome-wide RNA structure probing technologies that are yielding new insights into the structural landscape of the transcriptome. Finally, we discuss how these RNA 'structomic' methods can address emerging questions in RNA systems biology, from the mechanisms behind long non-coding RNAs to new bases for human diseases.